Ionic Liquids for SO2 Capture: Development and Progress: A Review - Lin, Hong; Bai, Peng; Guo, Xianghai (Asian Journal of Chemistry, 2014)
Removal of SO2 from flue gas has attracted increasing interests under worldwide environmental pressure. In this paper, the recent progress of ionic liquids for SO2 capture, including the absorption capacity, the desorption performance and the absorption mechanisms of guanidinium based ionic liquids, hydroxyl ammonium ionic liquids, imidazolium based ionic liquids and quaternary ammonium based ionic liquids, are reviewed. In addition, some strategies recently developed to enhance the absorption processes have been briefly introduced, such as ionic liquids mixtures, solidified ionic liquids and supported ionic liquids membranes. Moreover, the drawbacks for the industrial application of this technology have been proposed.